The Importance Of Financial Management For Companies - Zainal Zainal (Pusat Riset dan Inovasi Nasional, 2024)
Good financial management is very important for companies to achieve long-term financial goals. The goal of financial management is to maximize corporate value and ensure business continuity by managing financial resources effectively and efficiently. This article will discuss the importance of financial management for companies, including the need to manage budgets, identify financial resources, manage risk, and perform sound financial analysis. In conclusion, good financial management can help companies achieve long-term financial success and maximize company value.